Three New Depsipeptides, Homiamides A–C, Isolated from Streptomyces sp., ROA-065 - Jeong-Hyeon Kim; Ji Young Lee; Juri Lee; Prima F. Hillman; Jihye Lee; Byeongchan Choi; Man-Jeong Paik; Songyi Lee; Sang-Jip Nam (Molecules)
Three new depsipeptides, homiamides A–C (1–3), were isolated from a marine sediment-derived strain of Streptomyces sp., ROA-065. The planar structures of homiamides A–C (1–3) were elucidated using mass spectrometry (MS) and nuclear magnetic resonance (NMR) spectroscopic data. The absolute configurations of 1–3 were deduced from the application of the Marfey’s method and GC-MS analysis after formation of the O-trifluoroacetylated (S)-(+)-methyl-2-butyl ester derivatives of amino acids. Compounds 1–3 exhibited weak anti-bacterial activities against both Gram-positive bacteria and Gram-negative bacteria, with compound 1 showing MIC values of 32–64 μg/mL. In antifouling assays, compounds 1 and 2 displayed moderate activity against Micrococcus luteus KCTC 3063, while compound 3 exhibited weak activity against all tested bacteria.